Little baby Bobby - Van Laan, Nancy; Cornell, Laura (New York : Knopf : Distributed by Random House, 1997)
When a bouncy baby$1 (Bs buggy goes whooshing down a hill, he is in for quite a ride as an assortment of people give chase.s
Keywords: Babies -- Fiction; Stories in rhyme